Global Green Diplomacy Cross-Border Collaboration in Mangrove Conservation as a Blue Carbon Solution - LAKSMI, Putu Ayu Sita; PUTRA, I Ketut Johny Pramananda; KUSUMA, A.A Made Indra Wijaya; BAKAR, Mohd Azlan Bin Abu; AGASTIRA, Gusti Ngurah Danan (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
The existential challenge of climate change demands urgent solutions, with mangrove conservation emerging as a potent nature-based strategy through the Blue Carbon paradigm. This article explores the transformative concept of "Global Green Diplomacy" through a community service initiative in Bali, Indonesia, employing a Participatory Action Research (PAR) framework. It demonstrates how cross-border collaboration in mangrove conservation transcends mere ecological restoration to become a strategic, scalable, and indispensable Blue Carbon solution. The PAR methodology engaged local communities in five iterative phases: collaborative site assessment, co-design of the conservation plan, capacity building and cross-border knowledge exchange, hands-on implementation embodying the spirit of gotong-royong (cooperation), and participatory monitoring. Results revealed the successful rehabilitation of over 15,000 mangrove saplings across a five-hectare degraded zone, achieving a 78% survival rate. This grassroots action not only restored ecological functions—evidenced by increased biodiversity and a 60% reduction in plastic debris—but also spurred socio-economic transformation, notably through a community-managed ecotourism program. The discussion underscores that this local action gains global significance when linked to Blue Carbon and Green Diplomacy frameworks. The community's stewardship creates a verifiable carbon sink, unlocking opportunities for ethical financing via carbon credit schemes involving international partners. The study concludes that the synergy between local empowerment, cross-border collaboration, and global incentives is key to amplifying climate resilience, effectively turning grassroots action into a sustainable and scalable climate solution.